2018
DOI: 10.1002/anie.201806399
|View full text |Cite
|
Sign up to set email alerts
|

Guest‐Induced Structural Transformations in a Porous Halogen‐Bonded Framework

Abstract: Structural evidence obtained from in situ X-ray diffraction shows that halogen bonding is responsible for the formation of a dynamic porous molecular solid. This material is surprisingly robust and undergoes reversible switching of its pore volume by activation or by exposure to a series of gases of different sizes and shapes. Volumetric gas sorption and pressure-gradient differential scanning calorimetry (P-DSC) data provide further mechanistic insight into the breathing behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 88 publications
2
42
0
1
Order By: Relevance
“…Barbour et al reported reversible switching of the pore volume in porous halogen-bonded framework that was induced using gas adsorption switching. [334] Aida et al reported that a CH•••N bonded porous crystalline solid, prepared using D 3h -symmetric molecule (Py6Mes) with a nonpolar mesitylene core and 6 pendant, polar, pyridyl-rings, could be transformed between a porous open polymorph (Py open ) and nonporous closed polymorph (Py close ) in the solid state, taking advantage of the extremely labile CH•••N bonding interactions in the structure (Figure 26). [32] For example, MeCN vapor was used to generate the Py open polymorph, and a heat-induced transformation at 202 °C was used to generate Py close polymorph.…”
Section: Solid-state Transformations In Porous Molecular Solidsmentioning
confidence: 99%
“…Barbour et al reported reversible switching of the pore volume in porous halogen-bonded framework that was induced using gas adsorption switching. [334] Aida et al reported that a CH•••N bonded porous crystalline solid, prepared using D 3h -symmetric molecule (Py6Mes) with a nonpolar mesitylene core and 6 pendant, polar, pyridyl-rings, could be transformed between a porous open polymorph (Py open ) and nonporous closed polymorph (Py close ) in the solid state, taking advantage of the extremely labile CH•••N bonding interactions in the structure (Figure 26). [32] For example, MeCN vapor was used to generate the Py open polymorph, and a heat-induced transformation at 202 °C was used to generate Py close polymorph.…”
Section: Solid-state Transformations In Porous Molecular Solidsmentioning
confidence: 99%
“…Porous organic cages, 1 one of the most important subclasses of porous molecular materials, [2][3][4][5] have been recognized as an attractive functional material which could be complementary to established porous network polymers and frameworks (such as metal-organic frameworks (MOFs), 6 covalent organic frameworks (COFs) 7,8 or porous organic polymers (POPs) 9 ) because of their distinct features like high porosity, good chemical stability, and solution processability. Different from network polymers and frameworks, organic cages contain "extrinsic" and "intrinsic" pores, which refer to the pores located between molecules or within molecules, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Barbour and coworkers reported a porous halogenbonded framework, which was obtained by evaporating an acetone solution of 8 and 9 (Figure 7). 69 The evaporation produced a solvated yellow porous molecular crystal, wherein I these PMCs can be transformed to nonporous crystals by exposure to CH 2 Cl 2 , which also results in the turning ON of red luminescence. Such change can be reversed by exposing the nonporous crystals to hexafluorobenzene.…”
Section: Review Porous Molecular Crystalsmentioning
confidence: 99%